PEMBUDAYAAN KESUKARELAWANAN DALAM KALANGAN MASYARAKAT : SATU KAJIAN ULASAN SISTEMATIK (Volunteerism Enculturation among Community Member : A Systematic Review) - Tharshini, N. K.; Fauziah, Ibrahim (UTEM, 2019)
This article is prepared to review the volunteerism enculturation among community member. A systematic review was conducted to obtain information regarding the catalyst factors that contribute towards volunteerism enculturation among community member in databases such as Elsevier dan Sage. The results indicate that factors such as psychological needs, the need for recognition and reward and religious belief contributes towards volunteerism enculturation among community member. As an overall impact, the study provided implications to the concerned parties regarding the importance of volunteerism enculturation in order to instill social transformation and produce a caring, responsible and selfless community members.